2020
DOI: 10.1038/s41467-020-18742-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics prediction of immune-related adverse events during checkpoint immunotherapy

Abstract: Immune-related adverse events (irAEs), caused by anti-PD-1/PD-L1 antibodies, can lead to fulminant and even fatal consequences and thus require early detection and aggressive management. However, a comprehensive approach to identify biomarkers of irAE is lacking. Here, we utilize a strategy that combines pharmacovigilance data and omics data, and evaluate associations between multi-omics factors and irAE reporting odds ratio across different cancer types. We identify a bivariate regression model of LCP1 and AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
132
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 144 publications
(135 citation statements)
references
References 38 publications
2
132
0
1
Order By: Relevance
“…It is suggested that T cell receptor (TCR) diversity, CD8 + T cell clonal expansion and tumor mutation burden (TMB) may potentially predict irAE, although this is based on a single factor or under limited circumstances. Therefore, there is a lack of comprehensive methods to identify irAE biomarkers (12). The main aspects of irAE management include toxicity identification and classification, immunosuppression, and personalized modification of ICI management.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that T cell receptor (TCR) diversity, CD8 + T cell clonal expansion and tumor mutation burden (TMB) may potentially predict irAE, although this is based on a single factor or under limited circumstances. Therefore, there is a lack of comprehensive methods to identify irAE biomarkers (12). The main aspects of irAE management include toxicity identification and classification, immunosuppression, and personalized modification of ICI management.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recently, Jing et al reported that the combination of lymphocyte cytosolic protein 1 and adenosine diphosphate dependent glucokinase is a promising biomarker for irAEs. 27 However, biomarkers for predicting early-and late-onset CIP have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also used data sources beyond clinical trial data, such as patient studies and pharmacovigilance data combined with omics data, to identify intestinal microbiome profiles, tumor immune biomarkers, and differential gene expression associated with elevated irAE risk. [18][19][20] Barriers to aggregating irAE clinical trial data Clinical investigators face several challenges related to nomenclature and definitions of toxicity in capturing the characteristics and severity of irAEs. In general, the goldstandard mechanism that can definitively diagnose irAEs, and thus confirm that the toxicity is due to ICI treatment, and not a combination treatment partner such as chemotherapy or an alternative diagnosis, is biopsy with histopathological evidence of inflammation.…”
Section: Improving Clinical Trial Data Reporting: Standardizing Ae Terminology and Case Report Forms Would Facilitate Pooled Analyses Of mentioning
confidence: 99%